Chemical, physical, and mechanical properties of belangke bamboo (Gigantochloa pruriens) and its application as a reinforcing material in particleboard manufacturing - Iswanto, Apri Heri; Madyaratri, Elvara Windra; Hutabarat, Nicko Septuari; Zunaedi, Eka Rahman; Darwis, Atmawi; Hidayat, Wahyu; Susilowati, Arida; Adi, Danang Sudarwoko; Lubis, Muhammad Adly Rahandi; Sucipto, Tito; Fatriasari, Widya; Antov, Petar; et al. (MDPI, 2022)
This study aimed to analyze the basic properties (chemical composition and physical and mechanical properties) of belangke bamboo (Gigantochloa pruriens) and its potential as a particleboard reinforcement material, aimed at increasing the mechanical properties of the boards. The chemical composition was determined by Fourier transform near infrared (NIR) analysis and X-ray diffraction (XRD) analysis. The physical and mechanical properties of bamboo were evaluated following the Japanese standard JIS A 5908 (2003) and the ISO 22157:2004 standard, respectively. The results showed that this bamboo had average lignin, holocellulose, and alpha-cellulose content of 29.78%, 65.13%, and 41.48%, respectively, with a degree of crystallinity of 33.54%. The physical properties of bamboo, including specific gravity, inner and outer diameter shrinkage, and linear shrinkage, were 0.59%, 2.18%, 2.26%, and 0.18%, respectively. Meanwhile, bamboo’s mechanical properties, including compressive strength, shear strength, and tensile strength, were 42.19 MPa, 7.63 MPa, and 163.8 MPa, respectively. Markedly, the addition of belangke bamboo strands as a reinforcing material (surface coating) in particleboards significantly improved the mechanical properties of the boards, increasing the modulus of elasticity (MOE) and bending strength (MOR) values of the fabricated composites by 16 and 3 times.